Magnitude and duration of the impact generated on the athletes' body during training in Ippon-Seoi-Nage judo technique - T. Piucco; S.G. Santos (Desafio Singular, 2010)
This exploratory study aimed to analyse the magnitude and duration of the impact generated on the athletes' body during training in Ippon-Seoi-Nage judo technique. Two black belt judo athletes were studied, the tori (the thrower) weighting 75 kg and having 19 years of practice, and the uke (the thrown) weighting 72 kg and having 15 years of practice. A Bruel & Kjaer 4321 Accelerometer Triaxial, fastened to the fist, hip and ankle of the uke, was used. Data were collected in the laboratory. Ten falls were performed for each of the three articulations investigated. The largest impact values were observed for the fist in the vertical axis (351.95 g) and the smallest values were for the hip anterior posterior axis (5.18g). Impact duration times were greater in the hip vertical axis (.58 s) with no differences for the impact on fist and ankle. Considering these high impact values as well as the high frequency of falls during judo training, it is suggested a reevaluation of this training pattern and the sort of tatami adopted, in order to decrease the resulting harmful effects over the time.